Transmembrane Helices Are an Overlooked Source of Major Histocompatibility Complex Class I Epitopes - Bianchi, Frans; Textor, Johannes; van den Bogaart, Geert (Frontiers in Immunology, 2017)
About a fourth of the human proteome is anchored by transmembrane helices to lipid membranes. Transmembrane helices require multiple hydrophobic residues for spanning membranes, and this shows a striking resemblance with the requirements for peptide binding to major histocompatibility complex (MHC) class I. It therefore comes as no surprise that bio-informatics analysis predicts an over-representation of transmembrane helices among strong MHC class I binders. Published peptide elution studies confirm that transmembrane helices are indeed presented by MHC class I. This raises the question how membrane proteins are processed for MHC class I (cross-)presentation, with current research focusing on soluble antigens. The presentation of membrane-buried peptides is likely important in health and disease, as transmembrane helices are considerably conserved and their presentation might prevent escape mutations by pathogens. Therefore, it could contribute to the disease correlations described for many HLA haplotypes.